Chemodiversity, Bioactivity and Chemosystematics of the Genus Inga (FABACEAE): A Brief Review - Lima, Nerilson M. [UNESP]; Santos, Vanessa N. C.; La Porta, Felipe A. (Brazilian Chemical Soc, 2018)
The Inga genus belongs to the Fabaceae family, subfamily Mimosoideae, Ingeae tribe, and comprises about 300 species, whose name derives from the indigenous terminology Anga or inga, which in reality means seed is involved. This genre has economic potential in reforestation, herbal medicine, energy production and supply. Many species of this genus are used by Amazonian tribes for the treatment of various diseases. The secondary metabolism of this kind attests to the presence of phenolic substances belonging to the class of flavonoids, anthocyanins, tannins, phenolic acids, terpene substances such as saponins, triterpenes, phytosteroids, nitrogenous as L-tyrosine derivatives, proline and pipecolic acids, which are considered chemical markers of the gender. Pharmacological studies show important biological properties of pharmaceutical and agronomic interest for species of this genus, particularly antioxidant, insecticide, antiparasitic, antimicrobial, allelochemicals, antifungal and antitumor. Therefore, this review paper aims to show the main bioactivities reported for the genus, the chemical diversity of their secondary metabolism and its chemotaxonomic relevance of nitrogenous substances in the genus Inga.
Keywords: pipecolic acid; chemodiversity; pharmacological activity; chemotaxonomy